Patient and Public Involvement in Research Evaluating Integrated Care for People Experiencing Homelessness: Findings From the PHOENIx Community Pharmacy Pilot Randomised‐Controlled Trial - Andrew McPherson; Vibhu Paudyal; Richard Lowrie; Helena Heath; Jane Moir; Natalie Allen; Nigel Barnes; Hugh Hill; Adnan Araf; Cian Lombard; Steven Ross; Sarah Tearne; et al. (Wiley, 2024)
ABSTRACT Introduction There is a paucity of research on and a limited understanding of patient and public involvement (PPI) in the context of research in homelessness and, in particular, direct involvement of people with lived and living experience of homelessness (PEH) as expert advisors. We aim to report on outcomes and reflections from lived experience advisory panel (LEAP) meetings and PPI activities, held throughout the study lifecycle of a pilot randomised‐controlled trial (RCT) focused on evaluating integrated health and practical support for PEH. Methods Community Pharmacy Homeless Outreach Engagement Non‐medical Independent prescribing Rx (PHOENIx Community Pharmacy RCT) is an integrated health and social care intervention for people experiencing homelessness who present to community pharmacy. Intervention includes weekly support from a pharmacist prescriber and a third sector support worker for up to 6 months. PPI activities undertaken throughout the study were documented, including outcomes of LEAP meetings. Outcome reporting followed Guidance for Reporting Involvement of Patients and the Public 2 Short Form (GRIPP2‐SF). Results In total, 17 members were recruited into the LEAP; six meetings (three in two study sites) were held. PPI input was also received through representation from homelessness third sector organisation staff as study co‐applicants and core membership in the trial steering committee. Together, the PPI activities helped shape the study proposal, design of study materials, data analysis and dissemination materials. LEAP panel members offered valuable input via their experience and expertise into the delivery and refinement of interventions. Although longitudinal input was received from some LEAP members, ensuring repeat attendance in the pre‐planned meetings was challenging. Conclusion People who face social exclusion and marginalisation can provide highly valuable input as equal partners in co‐design and delivery of interventions seeking to improve their health and well‐being. Fluid membership and flexible methods of seeking and incorporating advice can offer pragmatic approaches to minimising barriers to continued involvement in research. Patient or Public Contribution This study reports findings and learning relevant to involvement of people with lived and living experience of homelessness as advisors in a research study. It is important for researchers to offer fluid memberships and use diverse methods to receive input from lived experience members, as traditional PPI methodology may be insufficient to ensure inclusivity. Staff and volunteers from third sector organisations were important PPI partners who bring their experience based on frontline service provision, often as the first port of call for people experiencing severe and multiple disadvantage. Trial Registration ISRCTN88146807.